Pengaruh Sukuk dan Faktor Internal terhadap Profitabilitas Bank Syariah - Renanta Ivana Nanda Rusmawan; Endang Hatma Juniwati; Ade Ali Nurdin (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to determine the impact Sukuk and Islamic bank internal factors on the profitability BRI Syariah. This study used secondary data using BRI Syariah quarterly reports for the years 2011-2020. The independent variable used is Sukuk, CAR, FDR, NPF, and BOPO and the dependent variable used is ROE which is used as a measure of the profitability of Islamic banks. This study uses the SPSS program and uses multiple linear regression analysis. The results showed that sukuk, NPF, CAR, FDR, and BOPO simultaneously had an effect on ROE. While partially the issuance of sukuk and FDR has no significant effect on ROE, and NPF, CAR, BOPO has a negative and significant effect on ROE BRI Syariah.